2007
DOI: 10.1016/j.jana.2007.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Chilean University Students: Knowledge and Concern About HIV/AIDS

Abstract: According to a 2004 report by the Joint United Nations Programme on HIV/AIDS, Chile has an incipient HIV/AIDS epidemic. Regardless of the classification, every year the cumulative incidence of HIV/AIDS increases. Young Chileans have been the most affected group; still, their knowledge, attitudes, and concerns about HIV/AIDS are not known. This study describes Chilean university students' HIV/AIDS-related knowledge, their worry about getting the virus, and the correlation between both variables. A convenience s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0
10

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 15 publications
(13 reference statements)
3
11
0
10
Order By: Relevance
“…Findings from our pilot study were consistent with previously reported observational studies, in which the knowledge of HIV in students and health professionals from Chile and other countries has been weak in several domains (Chimango et al, 2009; Ferrer et al, 2007; Kaponda et al, 2009; Norr et al, 2006). In addition, interventions for health professions university students have also shown significant improvement in knowledge and positive attitudes after education (Pickles et al, 2009; Valois et al, 2001; Yiu et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Findings from our pilot study were consistent with previously reported observational studies, in which the knowledge of HIV in students and health professionals from Chile and other countries has been weak in several domains (Chimango et al, 2009; Ferrer et al, 2007; Kaponda et al, 2009; Norr et al, 2006). In addition, interventions for health professions university students have also shown significant improvement in knowledge and positive attitudes after education (Pickles et al, 2009; Valois et al, 2001; Yiu et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…The lack of awareness and concern about HIV prevalence in Chile was confirmed in a study by Ferrer and colleagues (2007), in which 45 university students filled out questionnaires related to HIV knowledge, attitude, and personal concern. Results revealed that these students had quite high levels of HIV-related knowledge, as 77% of participants earned scores of 81% or higher on the HIV knowledge portion of the questionnaire.…”
mentioning
confidence: 93%
“…These findings were also consistent with a study by Salgado de Snyder et al (20) demonstrating that while women had information regarding means of HIV/AIDS transmission and ways of prevention, they did not use their knowledge to evaluate, moderate, and substantially change their risk behavior. Although there are other studies in line with the above two studies (21, 22), there are also a few studies showing an association between knowledge and risk behaviors (2, 23). …”
Section: Discussionmentioning
confidence: 67%
“…Women living with a partner may view themselves as being in a secure, monogamous, and stable relationship. Consequently, they may not perceive a need to practice safe sex (Ferrer et al, 2007). Also, women living with partners may be afraid to suggest condom use because this could offend the partner and cause relationship problems.…”
Section: Discussionmentioning
confidence: 99%